Movement System Dysfunction Applied to Youth and Young Adult Throwing Athletes - Ashley E. Disantis; RobRoy Martin (North American Sports Medicine Institute, 2022)
Shoulder and elbow injuries in overhead athletes, especially baseball pitchers, have become more common and result in limited participation. Upper extremity injuries in baseball can occur secondary to high velocity repetitive loading at extreme ranges of motion causing microtrauma to the musculoskeletal structures. With the vast number of youth and young adult baseball players in the United States and the increasing number of throwing related injuries, it is crucial that clinicians can perform a movement system evaluation of the throwing motion. An adequate evaluation of the movement system as it relates to the throwing motion can provide insight into abnormal throwing mechanics and provide rationale for selecting appropriate interventions to address identified impairments that may lead to injury. The purpose of this clinical commentary is to present a recommended movement system evaluation that can be utilized during both pre-season and in-season to assess for modifiable injury risk factors in youth and young adult baseball players. # Level of Evidence 5